Epidemiological aspects of colorectal cancer in East Azerbaijan, Northwest Iran: five year survival analysis - Barnous, Ramin; Somi, Mohammad Hossein; Sanaat, Zohreh; Jabbaripoor, Pooneh; Dolatkhah, Neda; Dolatkhah, Roya (Universa Medicina, 2021)
BackgroundColorectal cancer (CRC) is the third most common cancer and the second leading cause of death from cancer in the world. Currently, CRC is the fourth most common cancer in men and the second common cancer in women of all ages in Iran. The aim of this study was to determine the epidemiologic profile of CRC along with CRC specific survival analysis. MethodsThis was an analytical cross-sectional study using the East Azerbaijan Population Based Cancer Registry database (EA-PBCR) as a source for data related to patients with a diagnosis of CRC. Colorectal cancer specific 1- to 5-year survival analysis and mortality rates were calculated. Log-rank test and Cox regression analysis was performed to test the equality of survival function and mortality hazard. ResultsA total of 2,366 newly diagnosed CRCs were registered during 3 years, with a male: female ratio of 1.31. Overall survival rate was 49.8%. One- to 5-year survival rates were 96.21%, 56.94%, 48.62%, 47.88% and 46.76% respectively. At multivariate level, after adjusting for all variables, regression analysis showed that the hazard of mortality in stage IV cancers was 46.44 times higher than that in stage I cancers (HR=46.44, 95% CI: 14.86-145.14, p=0.000). However, differences in patients’ age group and sex and the subsite of cancer did not create any statistically significant variation between groups in regards to mortality hazards (p>0.05). ConclusionThis study demonstrated that the stage and grade of CRC were important prognostic factors and that early screening and diagnosis of CRC were essential.